Intractable and highly active relapsing multiple sclerosis – role of alemtuzumab - Dubey D (Dove Medical Press, 2015)
Divyanshu Dubey,1 Christopher A Cano,1 Olaf Stuve1–3 1Department of Neurology and Neurotherapeutics, University of Texas Southwestern Medical Center, 2Neurology Section, VA North Texas Health Care System, Medical Service, Dallas, TX, USA; 3Department of Neurology, Klinikum rechts der Isar, Technische Universität München, Munich, Germany Abstract: Alemtuzumab is a humanized recombinant monoclonal antibody that was recently approved by the US Food and Drug Administration and the European Medicines Agency for the management of relapsing forms of multiple sclerosis (MS). It has been utilized for the management of chronic lymphocytic leukemia, bone marrow and renal transplantation, or graft versus host disease. Because of its immunomodulatory properties, it was brought into clinical development in MS. One Phase II (CAMMS223) and two Phase III clinical trials (CARE-MSI and -II) have evaluated the safety and efficacy of alemtuzumab in patients with relapsing–remitting MS. Even though its efficacy profile and long-lasting effect have attracted much interest among physicians and patients, it has significant potential adverse effects that may limit its use to patients with active disease. Here, we review the history of drug development of alemtuzumab. Furthermore, we outline the postulated mechanisms of action, clinical evidence, and safety of alemtuzumab for its use as a disease-modifying agent in active and highly active MS. Keywords: alemtuzumab, multiple sclerosis, monoclonal antibody, CD52, idiopathic thrombocytopenic purpura